Prognostic impact of tumour-infiltrating immune cells on biliary tract cancer - Goeppert, Benjamin; Frauenschuh, Lena; Zucknick, Manuela; Stenzinger, Albrecht; Andrulis, Mindaugas; Klauschen, Frederick; Jöhrens, Korinna; Warth, Arne; Renner, Michael Oskar; Mehrabi, Arianeb; Hafezi, Mohammadreza; Thelen, A.; et al. (British journal of cancer, 2013)
Biliary tract cancers (BTC) are relatively rare malignant tumours with poor prognosis. It is known from other solid neoplasms that antitumour inflammatory response has an impact on tumour behaviour and patient outcome. The aim of this study was to provide a comprehensive characterisation of antitumour inflammatory response in human BTC.